2021
DOI: 10.3390/jcm10173810
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Vitrification for Fertility Preservation in Women with Benign Gynecologic Disease: French Clinical Practice Guidelines Developed by a Modified Delphi Consensus Process

Abstract: International guidelines are published to provide standardized information and fertility preservation (FP) care for adults and children. The purpose of the study was to conduct a modified Delphi process for generating FP guidelines for BGD. A steering committee identified 42 potential FP practices for BGD. Then 114 key stakeholders were asked to participate in a modified Delphi process via two online survey rounds and a final meeting. Consensus was reached for 28 items. Among them, stakeholders rated age-speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…An increasing number of authors are focusing their research on FP for nonmalignant diseases [2]. Legrand et al reported that oocyte banking in women treated for benign ovarian tumors is an e cient strategy, with a mean of 7.0 (± 5.23 SD) cryopreserved oocytes per woman, irrespective of the histological type of tumor [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of authors are focusing their research on FP for nonmalignant diseases [2]. Legrand et al reported that oocyte banking in women treated for benign ovarian tumors is an e cient strategy, with a mean of 7.0 (± 5.23 SD) cryopreserved oocytes per woman, irrespective of the histological type of tumor [13].…”
Section: Discussionmentioning
confidence: 99%
“…The secondary endpoints were as follows: (1) the total number of COS cycles performed per woman; (2) the COS cycle cancellation rate for no ovarian response; (3) the oocyte retrieval failure rate; and (4) the CLBR per stimulation cycle with fertilized oocyte, including fresh and frozen embryo transfers.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…If an OMA is accidentally punctured, the needle should be immediately withdrawn and flushed with media and the collecting tube should be changed [ 32 ]. According to the French recommendations, drainage—with a technique such as sclerotherapy—rather than cystectomy should be performed in first line if OMAs are too bulky and/or if they prevent easy access to the ovaries for retrieval [ 13 ].…”
Section: Ovarian Pick-upmentioning
confidence: 99%
“…They recommend offering FP for bilateral OMA > 3 cm or an OMA on a single ovary. They also suggest doing so before cystectomy if the ovaries are easily accessible for retrieval, in order to increase the number of oocytes cryopreserved [ 13 ].…”
Section: Introductionmentioning
confidence: 99%